The filtration system of localization and glocalization for brand voice and brand communication - Jūlija Surikova; Sati Siroda (Universitas Negeri Yogyakarta, 2023)
For over half a century, there has been ongoing debate among communication professionals and theorists about the need for localization or globalization in brand communication. Both sides have argued about the most effective strategy for global brands in the global market, with no clear consensus on the optimal approach. This paper aims to examine the impact of localization and glocalization on brand voice. A qualitative study design was used, based on a content analysis of case studies involving globalization, localization, and glocalization. The study is exploratory in nature and uses inductive reasoning. Through case study analysis, it became apparent that localized and glocalized brand communication and brand voice are influenced by various factors such as cultural background, religion, national beliefs, political environment, regional languages, media policies, political restraints, and socioeconomic conditions. These factors act as